2008
DOI: 10.1007/s00464-008-9766-6
|View full text |Cite|
|
Sign up to set email alerts
|

Noninvasive management of obstructing ureteral stones using electromagnetic extracorporeal shock wave lithotripsy

Abstract: Emergency SWL represents an effective tool in the treatment of ureteral stones with hydronephrosis and slight renal impairment. Although complete stone clearance after one treatment still remains a difficult target, the actual role of SWL in the management of acute obstruction is to obtain ureteral canalization and renal function recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In their recent article on extracorporeal shock wave lithotripsy (ESWL) as a first-line single therapy for obstructive ureteral stones, Chiara and colleagues indicated that ESWL is an effective therapy for obstructive ureteral calculi, varying degrees of hydronephrosis, and impaired renal function [1]. The present article adds further support to the feasibility and safety of ESWL for calculus clearance and recovery of renal function [1].…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…In their recent article on extracorporeal shock wave lithotripsy (ESWL) as a first-line single therapy for obstructive ureteral stones, Chiara and colleagues indicated that ESWL is an effective therapy for obstructive ureteral calculi, varying degrees of hydronephrosis, and impaired renal function [1]. The present article adds further support to the feasibility and safety of ESWL for calculus clearance and recovery of renal function [1].…”
mentioning
confidence: 54%
“…The present article adds further support to the feasibility and safety of ESWL for calculus clearance and recovery of renal function [1]. It is evident that ESWL has become standardized and can guarantee acceptable perioperative morbidity, yielding reproducible results for treatment of ureteral calculi.…”
mentioning
confidence: 62%